The prevalence of persistence metopic suture (metopisim) among Kurdish populations of Erbil city. - Soran M Karim; Othman Omar; Muyesser Nuri; Tuqa Yousif Al-Sharef (Erbil Dental Journal, 2023)
Background and objective: A fully developed frontal bone consists mainly of two portions separated by a vertically oriented suture called metopic, frontal or inter-frontal suture, it’s considered to be the first skull suture to close metopic suture physiologically closes at different times of age and could occur from birth through age 8 years,In some individual (and as a normal variant) a persistent metopic suture can be seen in the midline running down the frontal bone and the condition is referred to as metopisim. The study aims to investigate the prevalence of metopisim among the Kurdish population of Erbil city,type of metopisim, gender and/or environmental or racialimpact will also be assessed.